Histology for the Visually Impaired: A Study Applying Models at Universities in Spain and Brazil - Comarú, Michele Waltz (2021)
Instituto Federal do Rio de Janeiro. Campus Mesquita, RJ, Brasil / Instituto de Educação da Universidade de Lisboa. Lisboa, Portugal.